2014
DOI: 10.1038/hortres.2014.27
|View full text |Cite
|
Sign up to set email alerts
|

An optimized procedure for plant recovery from somatic embryos significantly facilitates the genetic improvement of Vitis

Abstract: Plant regeneration from grapevine (Vitis spp.) via somatic embryogenesis typically is poor. Recovery of plants from Vitis rotundifolia Michx. (muscadine grape) is particularly problematic due to extremely low efficiency, including extended culture durations required for embryo–plant conversion. Poor plant recovery is an obstacle to the selection of improved genetically modified lines. Somatic embryos (SEs) of V. rotundifolia cultivar Delicious (Del-HS) and Vitis vinifera L cultivar Thompson Seedless (TS) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…Somatic embryogenesis is the most consistent approach for adventitious regeneration, and gene transfer in grapevines has been a continuous focus of development ( Tapia et al, 2009 ; Zhou Q. et al, 2014 ; Saporta et al, 2016 ). Recent research has sought to extend the protocols to varieties ( Carra et al, 2016 ; San Pedro et al, 2017 ), hybrids, and rootstocks ( Oláh et al, 2009 ), including some Vitis species, which were until very recently described as recalcitrant ( Li et al, 2014 ). Transgenic individuals were generated using somatic embryo masses ( Ren et al, 2016 ; Nakajima et al, 2017 ; Wang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Somatic embryogenesis is the most consistent approach for adventitious regeneration, and gene transfer in grapevines has been a continuous focus of development ( Tapia et al, 2009 ; Zhou Q. et al, 2014 ; Saporta et al, 2016 ). Recent research has sought to extend the protocols to varieties ( Carra et al, 2016 ; San Pedro et al, 2017 ), hybrids, and rootstocks ( Oláh et al, 2009 ), including some Vitis species, which were until very recently described as recalcitrant ( Li et al, 2014 ). Transgenic individuals were generated using somatic embryo masses ( Ren et al, 2016 ; Nakajima et al, 2017 ; Wang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…NN basal medium supplemented with 2.0 mg L -1 2, 4-D and 0.5 mg L -1 TDZ was the most effective for the induction of callus (92%) and shoot formation (+++). Several studies on Vitis rupestris (Olah et al, 2003), Vitis rotundifolia (Dhekney et al, 2011;Li et al, 2014) and Vitis vinifera (Vidal et al, 2009) has been similarly succeeded to obtain regeneration using leaves as explants. In agreement with our results, Mullaw et al (2010) reported that abundant embryogenic callus in wine grape was obtained from leaf and floral explants supplemented with 9.0 μM 2, 4-D +17.0 μM IASP in combination with either 1.0 μM BA or 1.0 μM TDZ in darkness.…”
Section: Discussionmentioning
confidence: 99%
“…Perbedaan respons embriogenesis somatik di antara genotipe banyak ditemukan pada berbagai jenis tanaman budi daya, di antaranya Vitis vinivera L. (Malabadi, Vijaykumar, Nataraja, & Mulgund, 2010), Vitis spp. (Li et al, 2014), Gossypium spp. (Ghaemi, Majid, Fallahian, & Bezdi, 2011), Ipomea batatas L. (Sefasi et al, 2012) dan Manihot esculenta Crantz (Ngugi et al, 2015;Mongomake, Doungous, Khatabi, & Fondong, 2015).…”
Section: Pengaruh Interaksi Genotipe Jenis Eksplan Dan Taraf Kinetiunclassified